Enhancing defense enzymes by fungal and bacterial biocontrol agents in cabbage against head rot disease caused by Sclerotinia sclerotiorum - Malathi, S; Satya, V K; Deivamani, M; Ahiladevi, P; Thangeswari, S (Plant Science Today, 2025)
The pathogen Sclerotinia sclerotiorum is the source of cabbage head rot disease, which causes significant economic loss in the Nilgiris district, Tamil Nadu. To manage the disease, biocontrol agents were isolated from the rhizosphere region of cabbage and the antagonistic properties were assessed for their capacity to control cabbage head rot under in vitro conditions. Trichoderma viride (Tv3) recorded 86% inhibition and Pseudomonas fluorescens (PfC5) inhibited 80% reduction of mycelial growth of Sclerotinia sclerotiorum. During storage, the effectiveness of different carrier materials in maintaining the population of these biocontrol agents was evaluated. In glasshouse studies, the use of biocontrol agents in combination (Seed treatment + Soil application with (PfC5 + Tv3) + Foliar spray with PfC5) significantly recorded maximum (72.50) per cent disease reduction. Upregulation of defense genes triggered the enzymes viz., polyphenol oxidase (PPO), peroxidase (POD), phenylalanine ammonia lyase (PAL) and phenol were accumulated in cabbage treated with fungal and bacterial biocontrol agents and reduced the head rot disease incidence in cabbage and increase the yield.